2020
DOI: 10.23937/2469-5769/1510066
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia in Exclusively Breastfed High-Risk Neonates - A Hospital-Based Study

Abstract: Background: Hypoglycemia is one of the commonest metabolic problems in contemporary neonatal medicine. In the majority of healthy neonates, the frequently observed low blood glucose concentrations are not related to any significant problem and merely reflect normal processes of metabolic adaptation to extrauterine life. However, when low blood glucose levels are prolonged or recurrent, they may result in acute systemic effects and may result in neurologic sequelae. Aims and Objectives: To find out the incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…In our study, 50% of LGA babies had at least one value of low blood sugars. In the study by Patel et al ,[ 22 ] the incidence of hypoglycemia in SGA neonate was 37.5%, in LGA neonate was 18%, in macrosomic neonates was 20%, in LBW neonates 24%, in infant of diabetic mother was 14% and in late pre-term was 14%. In the study by Ute et al ,[ 23 ] routine glucose testing was indicated in LGA newborn infants of nondiabetic mothers.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 50% of LGA babies had at least one value of low blood sugars. In the study by Patel et al ,[ 22 ] the incidence of hypoglycemia in SGA neonate was 37.5%, in LGA neonate was 18%, in macrosomic neonates was 20%, in LBW neonates 24%, in infant of diabetic mother was 14% and in late pre-term was 14%. In the study by Ute et al ,[ 23 ] routine glucose testing was indicated in LGA newborn infants of nondiabetic mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Studi Patel P et al menemukan 20% bayi makrosomia dan 18% bayi dengan berat lahir lebih besar dari usia gestasi mengalami hipoglikemia pada 24 jam pertama dan normal kembali saat 48 jam berikutnya. (22) Kayode-Adedeji B yang meneliti 290 bayi makrosomia mendapatkan bahwa hipoglikemia dan ikterik merupakan masalah yang sering muncul dan biasanya berkaitan dengan diabetes gestational pada ibu. (23) Hasil analisis bivariat pada penelitian ini menunjukkan adanya hubungan antara berat badan lahir bayi dan kejadian hipoglikemia.…”
Section: Pembahasanunclassified